Adsorption/desorption characteristics and simultaneous enrichment of orientin, isoorientin, vitexin and isovitexin from hydrolyzed oil palm leaf extract using macroporous resins - Che Zain, Mohamad Shazeli; Lee, Soo Yee; Chian, Ying Teo; Shaari, Khozirah (Multidisciplinary Digital Publishing Institute, 2021)
Oil palm leaves (OPL) containing flavonoid C-glycosides are abundantly generated as oil palm byproducts. The performances of three macroporous resins with different physical and chemical properties for the enrichment of isoorientin, orientin, vitexin, and isovitexin from acid-hydrolyzed OPL (OPLAH) extract were screened. The XAD7HP resin exhibited the best sorption capacities for the targeted flavonoid C-glycosides and was thus selected for further evaluation. Static adsorption using the XAD7HP resin under optimal conditions (extract adjusted to pH 5, shaken at 298 K for 24 h) gave adsorption kinetics that fit well with a pseudo-second-order kinetic model. The adsorption of isoorientin and orientin was well described by Langmuir isotherms, while vitexin and isovitexin fit well with the Freundlich isotherms. Dynamic sorption trials using the column-packed XAD7HP resin produced 55–60-fold enrichment of isovitexin and between 11 and 25-fold enrichment of isoorientin, vitexin, and orientin using aqueous ethanol. The total flavonoid C-glycoside-enriched fractions (enriched OPLAH) with isoorientin (247.28–284.18 µg/mg), orientin (104.88–136.19 µg/mg), vitexin (1197.61–1726.11 µg/mg), and isovitexin (13.03–14.61 µg/mg) showed excellent antioxidant free radical scavenging activities compared with their crude extracts, with IC50 values of 6.90–70.63 µg/mL and 44.58–200.00 µg/mL, respectively. Hence, this rapid and efficient procedure for the preliminary enrichment of flavonoid C-glycosides by using macroporous resin may have practical value in OPL biomass waste utilization programs to produce high value-added products, particularly in the nutraceuticals, cosmeceuticals, pharmaceuticals, and fine chemicals industries.